SPEECH PROCESSING IN THE GSM STANDARD - St. Ave. Larisa Aleksandrovna Korotkova; Samandar Khikmatov (European Science Publishing, 2025)
This article is devoted to speech processing processes in the GSM standard, which are aimed at ensuring high quality of transmitted messages and implementing additional service capabilities, as well as improving the consumer qualities of subscriber terminals.
Keywords: DTX – Discontinuous Transmission, VAD – Voice Activity Detector, LPC – Linear Predictive Coding.